Pengaruh Tayangan Drama Korea True Beauty Terhadap Minat Beli Produk K-Beauty - Riahta Octaviani; Zainal Abidin; Flori Mardiana Lubis (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2021)
This research is motivated by the writer interest in Korean drama shows. So finally doing research to see the impact on one of the communities in Cikarang, namely the TnT Label Community, which is basically a K-pop dance cover community. So the purpose of this study is to find out whether there is an effect of the drama True Beauty on buying interest in K-Beauty products in the TnT Label dance cover community. This research was conducted with a quantitative method using an explanatory survey. The purpose of this study was to find out how the influence of Korean drama True Beauty on buying interest in K-Beauty products. The theory used in this research is IMC (Integrated Marketing Communication) Theory. The population in this study were all members of the TnT Label Community in Cikarang. Data collection was obtained through the distribution of questionnaires and literature study.